2022
DOI: 10.3390/foods11030381
|View full text |Cite
|
Sign up to set email alerts
|

Novel Insights into the Differences in Nutrition Value, Gene Regulation and Network Organization between Muscles from Pasture-Fed and Barn-Fed Goats

Abstract: The physiological and biochemical characters of muscles derived from pasture-fed or barn-fed black goats were detected, and RNA-seq was performed to reveal the underlying molecular mechanisms to identify how the pasture feeding affected the nutrition and flavor of the meat. We found that the branched chain amino acids, unsaturated fatty acids, and zinc in the muscle of pasture-fed goats were significantly higher than those in the barn-fed group, while the heavy metal elements, cholesterol, and low-density lipo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 48 publications
0
14
0
Order By: Relevance
“…This implies that pasture grazing enhances the meat flavor of goat kids. Yang et al [ 87 ] also showed that, compared with their stall-fed counterparts, pasture-grazed goat kids had superior flavor in regard to the longissimus muscle, which can be attributed to lower isoleucine and leucine contents. These outcomes could be because walking during pasture grazing promotes lipid oxidation in meat, increasing the synthesis of aldehyde and alcohol compounds [ 87 ] and resulting in different FA compositions of the meat [ 88 ].…”
Section: Feeding Systems Of Small Ruminants Affect Organoleptic Quali...mentioning
confidence: 99%
See 4 more Smart Citations
“…This implies that pasture grazing enhances the meat flavor of goat kids. Yang et al [ 87 ] also showed that, compared with their stall-fed counterparts, pasture-grazed goat kids had superior flavor in regard to the longissimus muscle, which can be attributed to lower isoleucine and leucine contents. These outcomes could be because walking during pasture grazing promotes lipid oxidation in meat, increasing the synthesis of aldehyde and alcohol compounds [ 87 ] and resulting in different FA compositions of the meat [ 88 ].…”
Section: Feeding Systems Of Small Ruminants Affect Organoleptic Quali...mentioning
confidence: 99%
“…Yang et al [ 87 ] also showed that, compared with their stall-fed counterparts, pasture-grazed goat kids had superior flavor in regard to the longissimus muscle, which can be attributed to lower isoleucine and leucine contents. These outcomes could be because walking during pasture grazing promotes lipid oxidation in meat, increasing the synthesis of aldehyde and alcohol compounds [ 87 ] and resulting in different FA compositions of the meat [ 88 ]. In addition, compared with intensive feeding on concentrate diets, grazing pasture with concentrate supplementation exhibited a similar flavor effect on goat kids [ 53 ], possibly because of the similar meat IMF content between the two feeding systems [ 89 , 90 ].…”
Section: Feeding Systems Of Small Ruminants Affect Organoleptic Quali...mentioning
confidence: 99%
See 3 more Smart Citations